Réponses

2012-10-18T20:41:28+02:00

2(x+3)=5x                                                          1-9(t+6)=-2(4-3t)

2x+6=5x                                                             1-9t-54=-8+6t

6=5x-2x                                                              8-53=6t+9t

6=3x                                                                   -45=15t

x=6 sur 3                                                             t=-45 sur 15

x=2                                                                     t=-3